Exploring teaching engineering in English at a Spanish university: perspectives of students and lecturers on challenges and opportunities - Carmela Oria Alonso; Lucila María Pérez Fernández (Discover Education)
Abstract The persistent challenge of English proficiency in Spain, particularly in higher education, has gained critical importance due to global industry demands. Despite over 15 years of English-Medium Instruction (EMI) initiatives under the European Higher Education Area framework, linguistic shortcomings remain prevalent. This study examines the perceptions of engineering students and lecturers at a Spanish public university regarding EMI, focusing on the institution’s role in fostering language competencies, influential factors, and areas for improvement. A survey was conducted with 311 of 2,090 students from various engineering degrees and age groups, including those with and without prior EMI experience, as well as 30 of 45 lecturers with diverse professional backgrounds. Data analysis, performed using Python, reveals that students frequently lack sufficient English skills and emphasise the need for stronger institutional support. Lecturers highlight insufficient pedagogical training and the challenges of linguistic heterogeneity among students. Statistical findings underscore the necessity for specialised lecturer training, interdisciplinary collaboration, and a student-centred approach to EMI. The study concludes that Spanish public universities cannot assume incoming students possess adequate language skills. Effective EMI implementation requires addressing lecturers’ training needs and providing robust linguistic support for students. These insights contribute to enhancing EMI practices in higher education.